2016
DOI: 10.1186/s12860-016-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of hif-1 promotes resistance to the exogenous mitochondrial stressor ethidium bromide in Caenorhabditis elegans

Abstract: BackgroundMitochondrial dysfunction is one of the leading causes of neurological disorders in humans. Mitochondrial perturbations lead to adaptive mechanisms that include HIF-1 stabilization, though the consequences of increased levels of HIF-1 following mitochondrial stress remain poorly understood.ResultsUsing Caenorhabditis elegans, we show that a hif-1 loss-of-function mutation confers resistance towards the mitochondrial toxin ethidium bromide (EtBr) and suppresses EtBr-induced production of ROS. In mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Using a mitochondrial membrane permeabilization assay, they found that several organophosphate compounds used in flame retardants caused defects in mitochondrial function in the nematode. Kamal et al (2016) showed an interaction between hif-1 and the mitochondrial dysfunction caused by ethidium bromide in the nematode. While these studies are of divergent compounds, they again show the usefulness of a strong genetic model such as the nematode for performing initial studies of the interactions between genetics and environmental toxicology.…”
Section: Toxicologymentioning
confidence: 99%
“…Using a mitochondrial membrane permeabilization assay, they found that several organophosphate compounds used in flame retardants caused defects in mitochondrial function in the nematode. Kamal et al (2016) showed an interaction between hif-1 and the mitochondrial dysfunction caused by ethidium bromide in the nematode. While these studies are of divergent compounds, they again show the usefulness of a strong genetic model such as the nematode for performing initial studies of the interactions between genetics and environmental toxicology.…”
Section: Toxicologymentioning
confidence: 99%
“…A prominent theory used to explain the aging process is the "free radical theory of aging" (1). This theory is based on findings that the cumulative oxidative damage caused by oxygen free radicals, a byproduct of cellular respiration occurring in mitochondria, speeds up the aging process (2)(3). Specifically, during cellular respiration, oxygen free radicals are released as a side product of oxidative phosphorylation, the process used to generate ATP.…”
Section: Introductionmentioning
confidence: 99%